2014
DOI: 10.4236/mrc.2014.32007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZSM-22 in Static and Dynamic System Using Seeds

Abstract: ZSM-22 was synthesized using various sources of silica, organic template 1,6-diaminohexane, under hydrothermal conditions, with and without agitation during crystallization. Subsequently, the crystallized material was used as seeds to accelerate the crystallization process. Characterization of the ZSM-22 samples was performed by XRD, ATG/DTG and FT-IR. It was found that it is possible to synthesize ZSM-22 employing colloidal silica and pyrolytic silica as silicon sources only if the system is stirred during cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is probably due to the plausible isomorphous substitution of Si 4+ and al 3+ during calcination in the zeolite framework. Small bands at around 1710 cm −1 can be traced to the insignificant vibration of Al-O-Al, amounting to lower aluminium species in the zeolite structure [65,66]. Meanwhile, Figure 3b displayed identical FTIR spectra of ZSM/PES membranes.…”
Section: Atr-ftir Analysismentioning
confidence: 91%
“…This is probably due to the plausible isomorphous substitution of Si 4+ and al 3+ during calcination in the zeolite framework. Small bands at around 1710 cm −1 can be traced to the insignificant vibration of Al-O-Al, amounting to lower aluminium species in the zeolite structure [65,66]. Meanwhile, Figure 3b displayed identical FTIR spectra of ZSM/PES membranes.…”
Section: Atr-ftir Analysismentioning
confidence: 91%
“…To resolve these drawbacks, the seed-assisted method has been applied to decrease the crystallization time and optimize the synthetic conditions. 29,30 The seed-assisted process is relatively simple and requires few raw materials. Many previous reports have demonstrated that Mn-based composite oxides exhibit great advantages in soot combustion and low-temperature SCR because of their low cost and good oxidation/reduction ability resulting from the variable valence state of Mn (Mn 4+ , Mn 3+ , and Mn 2+ ).…”
Section: Introductionmentioning
confidence: 99%
“…Although unmodified poly­(methyl methacrylate) (PMMA) as a macroporous template does not need a complex synthesis process, this may decrease the crystallization temperature of zeolite and extend the crystallization time. To resolve these drawbacks, the seed-assisted method has been applied to decrease the crystallization time and optimize the synthetic conditions. , The seed-assisted process is relatively simple and requires few raw materials. Many previous reports have demonstrated that Mn-based composite oxides exhibit great advantages in soot combustion and low-temperature SCR because of their low cost and good oxidation/reduction ability resulting from the variable valence state of Mn (Mn 4+ , Mn 3+ , and Mn 2+ ). Therefore, the combination of 3DOM ZSM-5 and Mn-based oxides is a promising approach for the removal of NO x and soot simultaneously.…”
Section: Introductionmentioning
confidence: 99%